2001
DOI: 10.1080/02726350152772083
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Bulk Mechanical Properties and Modeling the Load-Response of Rootzone Sands. Part 1: Round and Angular Monosize and Binary Mixtures

Abstract: The bulk mechanical properties of two different types of rootzone sands (round and angular) were measured using a cubical triaxial tester. T wo monosize sands (d 50 = 0:375 mm and 0.675 mm) and their 50:50 binary mixtures (d 50 = 0:500 mm) were studied. T he compression, shear, and failure responses of the above-mentioned six compositions were analyzed, compared, and modeled. T wo elastic parameters (bulk and shear moduli) and two elastoplastic parameters (swelling and consolidation indices) of the six sand co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
4
8
0
Order By: Relevance
“…Effect of particle size on compact strength has been well documented (Khan and Pilpel, 1986;McKenna and McCafferty, 1982). In addition, effect of particle shape on a powder system has been investigated in detail, as well (de Bono and McDowell, 2016;Mittal et al, 2001;Yi et al, 2002;Yi et al, 2001). However, study on the relationship between particle shape and compact's properties is scarce, which is thought to be because of the difficulty in quantification of particle shape.…”
Section: Quality: Strengthmentioning
confidence: 99%
“…Effect of particle size on compact strength has been well documented (Khan and Pilpel, 1986;McKenna and McCafferty, 1982). In addition, effect of particle shape on a powder system has been investigated in detail, as well (de Bono and McDowell, 2016;Mittal et al, 2001;Yi et al, 2002;Yi et al, 2001). However, study on the relationship between particle shape and compact's properties is scarce, which is thought to be because of the difficulty in quantification of particle shape.…”
Section: Quality: Strengthmentioning
confidence: 99%
“…Additionally, Yi et al (2001) stated that (1) irregularly shaped particles can readily lodge in the interstitial void spaces, and (2) void spaces formed from irregularly shaped coarse particles are larger than those for spherically shaped particles.…”
Section: Development Of Mechanistic Theory and Dimensional Analysis-bmentioning
confidence: 99%
“…Particle shape has substantial influence on golf course putting green and athletic field root‐zone performance. Research with mono‐sized and mixed‐sized samples has indicated that sands with increasing angularity exhibit lower bulk densities and higher total porosities (Zhang and Baker, 1999; Yi et al, 2001; Puri and Mancino, 2002). Variance in particle shape complexity has also been reported to yield differences in the hydraulic conductivity of sand root‐zone mixes, with more angular and spherical material exhibiting higher permeability than less angular and less spherical material (Zhang and Baker, 1999).…”
mentioning
confidence: 99%
“…The influence of particle shape on bulk modulus values has also been shown in mixed‐sized samples. Round, binary sand mixes have a greater resistance to compaction than angular, binary mixes (Yi et al, 2001). The mixes of round particles are able to fill more of the voids than the angular mixes, which results in less volume change under load (Yi et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation